Impact of Concurrent Genomic Alterations on Clinical Outcomes in Patients With ALK-Rearranged NSCLC - Lara-Mejía, L (2024)
Introduction: ALK tyrosine kinase inhibitors have exhibited promising activity against advanced ALK-rearranged NSCLC. However, co-occurring genetic alterations, such as CDKN2A/B or TP53, may negatively affect the efficacy of targeted therapies. Methods: From December 2017 to December 2022, this study cohort analyzed next-generation sequencing data of 116 patients with metastatic ALK-rearranged NSCLC from five Latin American cancer centers. Clinicopathologic and molecular features were associated with clinical outcomes and risk of brain metastasis (BrM) in patients with and without concurrent somatic alterations. Results: All patients (N = 116) received a second-generation ALK tyrosine kinase inhibitor, and alectinib was selected in 87.2% of cases. Coalterations occurred in 62% of the cases; the most frequent were TP53 mutations (27%) and CDKN2A/B loss (18%). The loss of CDKN2A/B was associated with an increased risk of BrM, with a cumulative incidence of 33.3% versus 7.4% in the non-coaltered subgroup. Compared with patients without coalterations, patients with concurrent CDKN2A/B loss (n = 21) had a shorter median progression-free survival (10.2 versus 34.2 mo, p < 0.001) and overall survival (26.2 versus 80.7 mo, p < 0.001). In the multivariate analysis, co-occurring CDKN2A/B loss was associated with poorer progression-free survival and OS despite the presence of other somatic coalterations, TP53 mutations, BrM, and Eastern Cooperative Oncology Group Performance Status. Conclusions: This study confirmed the worse prognostic value, which depicted co-occurring alterations in patients with ALK rearrangement. CDKN2A/B loss was substantially associated with worse outcomes and a higher risk of brain metastases. The evidence presented in our study may help select patients with ALK-positive tumors suitable for treatment escalation and closer brain follow-up.